Evaluation of the psychometric properties of the cardiac distress inventory in Iranian patients with heart disease - Hamid Sharif-Nia; João Marôco; Alun C. Jackson; Safoura Salehi; Omolhoda Kaveh; Fateme Miraghai; Seyed Hamzeh Hosseini (Scientific Reports)
Abstract Psychological distress is common among patients with heart disease, necessitating valid and reliable assessment tools for measuring cardiac distress. The Cardiac Distress Inventory (CDI) has been developed for this purpose, but its psychometric properties require validation in different cultural contexts. This study aimed to evaluate the psychometric properties of the Farsi version of the CDI in an Iranian population with heart disease, focusing on its validity, reliability, and factor structure. A cross-sectional study was conducted from October to December 2024 with 400 adult patients diagnosed with heart disease. Participants were recruited from cardiac departments and clinics using convenience sampling. The CDI was translated into Farsi following WHO guidelines and assessed for face and content validity. Exploratory factor analysis using Maximum Likelihood Estimation (MLEFA) with Promax rotation and confirmatory factor analysis were conducted to determine construct validity. Convergent and discriminant validity were examined using average variance extracted (AVE) and heterotrait-monotrait (HTMT) ratio, while reliability was assessed via Cronbach’s alpha, McDonald’s omega, and composite reliability. Measurement invariance across gender groups was also analyzed. The mean age of participants was 42.95 years (SD = 14.02), and 56.8% were women. EFA identified a two-factor structure—Existential and Emotional Distress and Uncertainty and Maladaptive Coping—explaining 69.15% of the variance, with 10 retained items. CFA confirmed the model fit (χ2 34 = 45.714, p = 0.086, CFI = 0.991, RMSEA = 0.036). The CDI demonstrated strong internal consistency (Cronbach’s alpha > 0.8) and good convergent (AVE > 0.5) and discriminant validity (HTMT = 0.374). Measurement invariance across gender was established at the configural, metric, and scalar levels. The Farsi version of the CDI is a valid and reliable tool for assessing cardiac distress in Iranian patients with heart disease. These findings support its use in clinical and research settings to better understand and address the psychosocial challenges faced by this population, ultimately improving psychological assessment and intervention strategies.